A comparison between Captopril, Valsartan, Carvedilol and Conventional therapy in the treatment of heart failure - Al-Mousilly M. Maiada (College of Pharmacy / Mustansiriyah University, 2005)
A comparison was done between captopril, valsartan, carvedilol & the conventional therapy in patients with heart failure. The difference was reflected on the survival rate and hospital admissions. Eighty patients were enrolled in this study, all were diagnosed as having heart failure (Class I - IV). They were grouped into four groups each consisted of 20 patients. group I were given captopril 25mg twice daily, group II were given valsartan 80mg once daily, group III had carvedilol 12.5mg twice daily, and group IV were given the conventional therapy (digoxin, diuretics, nitrates .... etc.). Blood pressure and heart rate were checked at baseline (before treatment) & after one and two months after initiation therapy. Data were compared to those of 15 healthy & subjects included in the study as well. Results revealed that a significant (p<0.05) reduction in blood pressure was noticed for the four groups. The heart rate was increased significantly (p<0.05) in the captopril & valsartan groups after two months while decreased significantly following carvedilol & conventional treatment. As a whole, a high percentage of improvement in the functional class of NYHA was found in the valsartan (80%) & the carvedilol (70%) groups, as no health deterioration was noticed in any of these two groups & no one died. While the improvement percentage was to a lesser extent among patients on captopril the conventional therapy (10% and 20% respectively) with reported deaths. The number of hospitalization during the follow up period was reduced significantly (p<0.001) in the valsartan and carvedilol groups and to a lesser extent in the captopril group while there was no significant reduction in hospital admissions of patients on the conventional therapy. According to this, carvedilol or valsartan improved cardiac function, quality of life, reduced mortality and morbidity in patients with heart failure leading to a better short & long term prognosis.